Intergenerational Communication Patterns between ‎Principals and Teachers in Improving Learning Quality: A ‎Systematic Literature Review - Dina Puspita; Muhammad Kristiawan; Eko Risdianto (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to map, synthesize, and analyze empirical evidence on intergenerational communication patterns between school principals (Baby Boomers, Generation X, Millennials) and teachers (Generation X, Millennials, Generation Z) and its impact on learning quality. Method: A systematic literature review was conducted following the PRISMA guidelines. A search of Google Scholar, ERIC, and Scopus databases (2017–2026) identified 487 articles, of which 25 met the inclusion criteria for in-depth analysis. Results: Findings reveal five key insights: (1) each generation exhibits distinct communication styles shaped by social context and technology adoption; (2) generational gaps create barriers in media preferences, formality norms, and feedback expectations; (3) Generation X principals employing care-based communicative leadership effectively bridge these differences; (4) multi-channel strategies, two-way mentoring, and an inclusive climate enhance cross-generational communication; and (5) effective intergenerational communication significantly improves teacher motivation, collaboration, and learning quality. Novelty: This study uniquely synthesizes cross-generational dynamics across four generations within school leadership, highlighting the underexplored role of Generation X principals as effective mediators. Practical Implication: Findings inform school management policies that are responsive to generational diversity, promoting adaptive communication frameworks. Contribution: The study contributes a consolidated evidence base on intergenerational communication in educational leadership, offering actionable strategies to improve learning quality through enhanced teacher-principal interactions.